A new economic growth engine for China : escaping the middle-income trap by not doing more of the same - Woo, Wing Thye (World Scientific ; Imperial College Press, 2012)
This volume is a report by leading international economic experts on China's economic priorities in the coming years. From various aspects of the domestic and foreign situation, China has now reached a critical juncture in its economic development. Unless China is able to overcome the difficulties in undertaking further reforms in the next ten years, China would be caught in the middle-income trap and be unable to become a modern country. The future course of China's economic development is also of great concern to the rest of the world because the socio-political-economic conditions in China.